April Fools and KCPR Auction, 1978 (1978)
[00:00] Poly People - Donna Pagburn, Randy Kerdoon [03:28] 91 Entertainment - Cheryl Klien [06:59] Pal's Stereo - Mark Wurfl, Frank Thomas, Debbie Silk [07:50] Kevin and Kevin Sports - Kevin Riggs, Kevin Falls [10:47] Disclaimer - Dave Kerley [11:08] News Intro - Chuck Schwynoch, Dave Kerley [11:34] Studio 229, City Councilmen speaks - Kevin Falls, Kevin Riggs [13:35] News Intro - Chuck Schwynoch, Dave Kerley [13:55] Campus News - Ace and Duce [17:40] Car Debate - Captain Allen, Kevin Allen, and Dave Allen [23:18] Music Break [23:25] Mark Allen Show - April Fool's Day Car Debate [28:48] Music Break [28:53] KCPR radio staff discussion [30:33] Disclaimer - Dave Kerley [30:49] Music Break [30:55] Studio 229 - Jam Names [33:11] City Councilmen speaks in Studio 229 [35:06] News Intro - Chuck Schwynoch, Dave Kerley [35:23] Campus News - Ace and Duce [39:24] Mix KCPR transitions and songs for April Fools [40:50] Mark Allen Show - April Fool's Day Washington Special Message [42:16] Disclaimer - Dave Kerley [42:38] Music Break [42:54] False Test for Sports Alerts [43:27] Music Break [43:37] Car Debate - Captain Allen, Kevin Allen, and Dave Allen [43:49] The Allen Women sing [47:45] News Intro - Chuck Schwynoch, Dave Kerley [47:56] Campus News - Ace and Duce [50:56] Songs from April Fools [51:59] The Allen Women speak on men [52:17] Plenty of Men [52:38] Music Break [52:49] The Allen Women speak [53:02] Songs from April Fools - Saturday Night [54:18] Gary Owens Auction ID's - Gary Owens, KMPC Los Angeles, KCPR